Liposomal Drug Delivery of a Major Component of Coconut Oil for the Treatment of Acne Vulgaris in vitro and in vivo - Pornpattananangkul, Dissaya (International Coconut Community, 2016)
Abundantly found in coconut oil, lauric acid (LA), a 12-carbon atom chain free fatty acid, has shown its potent antimicrobial activity against the acne-causing bacteria, Propionibacterium acnes (P. acnes). To facilitate the administration of LA and improve its efficacy, nanoliposomes were used to encapsulate LA. In this study, the antimicrobial activity of LA was compared with other free fatty acids and benzoyl peroxide (BPO). Subsequently, LA was incorporated into nano-sized bilayer lipid vesicle (lauric acid liposome, LipoLA). It was demonstrated that the antimicrobial activity of LA in LipoLA was enhanced at low LA concentration. Interaction study also showed that the liposome aids in the fusion between LA and the bacterial membrane, leading to an effective delivery of LA molecules to the target site. More interestingly, in vivo study indicates that antimicrobial activity of LipoLA is well preserved and higher than BPO. Since LA is a natural compound from coconut oil and liposomes have been successfully and widely applied as a drug delivery vehicle in the clinic, the LipoLA developed in this work holds great potential of becoming a safe and effective therapeutic medication for acne vulgaris and other P. acnes associated infections.